THE EFFECTIVENESS OF THE GUIDED DISCOVERY LEARNING (GDL) METHOD USING A CONTEXTUAL APPROACH REVIEWED FROM MATHEMATICAL CRITICAL THINKING ABILITY OF SENIOR HIGH SCHOOL IN MUNA DISTRICT - Agus, Imaluddin; Fitriani, Fitriani (IAIN Ambon, 2019)
Penelitian ini bertujuan untuk menguji efektivitas metode pembelajaran penemuan terbimbing menggunakan pendekatan kontekstual dalam hal keterampilan berpikir kritis siswa SMP. Jenis penelitian yang digunakan adalah eksperimen semu. Populasi dalam penelitian ini adalah semua siswa kelas VIII SMP di Kecamatan Kontukowuna, Kabupaten Muna, Sulawesi Tenggara pada tahun 2016/2017. Pengumpulan data diperoleh melalui penyediaan empat item pertanyaan instrumen tes keterampilan berpikir kritis, di mana setiap pertanyaan mewakili indikator kemampuan berpikir kritis dan lembar observasi pelaksanaan pembelajaran. Hasil penelitian dianalisis menggunakan uji t satu sampel. Temuan menunjukkan bahwa nilai uji t 2,719> (t_0,05,27) = 2,0518, yang dapat disimpulkan bahwa metode pembelajaran penemuan terbimbing efektif dalam hal kemampuan berpikir kritis siswa SMP. Hasil ini didukung oleh peningkatan rata-rata pretest 27,66 ke posttest 76,00 yang lebih tinggi dari kriteria penguasaan mengajar minimum (KKM) dari 70. Kata kunci: belajar penemuan, kontekstual, berpikir kritis, matematika This study aimed to test the effectiveness of guided discovery learning method using a contextual approach in terms of students' critical thinking skills of SMP. Type of research used was quasi experiment. Population in this research was all VIII grader students of Senior High School in sub-district Kontukowuna, Muna districts, Southeast Sulawesi in 2016/2017. Data collection was obtained through the provision of four items of question of critical thinking skills test instrumen, where each question represents an indicator of critical thinking ability and observation sheet of learning implementation. Research result was analyzed using one sample t test. The findings showed that t test value 2,719> (t_0.05,27) = 2.0518, which can be concluded that the guided discovery learning method was effective in terms of the critical thinking ability of junior high school students. This result was supported by the increase of average of pretest 27.66 to posttest 76.00 which was higher than the minimum teaching mastery criteria (KKM) of 70. Keywords: discovery learning, contextual, critical thinking, math